Feeder - Weekes, Patrick (Margaret K. McElderry Books, 2018)
Lori Fisher hunts monsters, aided by an interdimensional creature called Handler, but when she stumbles across the Nix, a kidnapped group of mutant teens, she becomes the hunted.